Suppose 15 = -2*g + 7*g. Solve j + 16 = -g*j for j.

-4

Suppose -h + 90 = 84. Solve 5*y - h = -1 for y.

1

Let x be 12/(-10)*(-120)/16. Suppose -3*n + x = -0*n. Solve -a = -n*a - 2 for a.

-1

Suppose 5*b - 23 = 3*n, 3*b + 2*b + 4*n = 16. Solve 3*s = 4*s - b for s.

4

Let n = -6 - -3. Let h be ((-4)/2)/(n/6). Solve -h*y - 3 = -y for y.

-1

Suppose 0*y - 2*o = -y + 1, -4*y - 1 = -3*o. Let p be (26)/(y/(-6)). Solve -w + p = -2*w for w.

-2

Let v(l) = 4*l**2 + l. Let f be v(1). Let h = -3 + f. Let q be -1 + 0 - (3 - 6)*1. Solve -h = g + q for g.

-4

Let l(m) = -m3 - 9*m2 - m - 6. Suppose -u - 5*w + 29 = 0, 5*u - 3*w - 13 - 20 = 0. Suppose 36 + u = -5*s. Let x be l(s). Solve 16 = -x*i - i for i.

-4

Let a(y) = -y3 - 8*y2. Let k be a(-8). Solve k = 2*t + 2*t for t.

0

Suppose m = -3*m. Suppose -6*o + o = m. Let t(j) = -5*j - 1. Let q be t(-1). Solve 20 = -o*w - q*w for w.

-5